Hispanic adults with type 2 diabetes mellitus using lipid-lowering agents have better periodontal health than non-users - Oelisoa M. Andriankaja; Kaumudi J. Joshipura; Michael A. Levine; Margarita Ramirez-Vick; Julio A. Rivas-Agosto; Jorge S. Duconge; Dana T. Graves (SAGE Publishing, 2023)
Background: Recent studies suggest that lipid-lowering agents (LLA) may reduce chronic periodontitis, but it is unknown whether this benefit extends to people with type 2 diabetes (T2D). Objective: We assessed the association between LLA use and periodontitis in Hispanic adults with T2D. Design: This was a cross-sectional observational study. Methods: We assessed the association of LLA use and periodontal parameters in 253 Puerto Ricans 40-65 years with T2D who participated in the Lipid-Lowering agents use in Periodontitis and Diabetes Study study. Participants were classified as (a) none- or <1 year, (b) 1-4 years, or (c) >4 years. The primary outcome consists of a tertile percent of sites with probing pocket depth (PPD) ⩾ 4 mm and the secondary outcome includes tertiles of percent sites with clinical attachment loss (CAL) ⩾ 4 mm. Multinomial logistic regression models adjusted for age, gender, smoking status, education, waist circumference, glycosylated hemoglobin A1C (HbA1c), bleeding on probing, examiner, and anti-inflammatory agents were used to estimate the association. Results: LLA (92.5%, statins) was used by 52% of participants. LLA use 1-4 years was associated with lower odds of PPD ⩾ 4 mm (OR: 0.22, p   =  0.005; high versus low tertile) or lower odds of CAL ⩾ 4 mm (OR: 0.33, p   =  0.02, middle versus low tertile), compared to those with LLA minimal or no use. This association was lost for participants who used LLA for >4 years. LLA users for >4 years with periodontal disease had elevated HbA1c (OR: 1.36, p   =  0.05). Conclusion: The use of LLA for 1-4 years was associated with lower values of periodontal parameters versus minimal LLA use. This association was not present among people using LLA > 4 years users, but these participants had poorer glycemic control compared to other participants. In this cross-sectional study, the finding that LLA use 1- 4 years is associated with lower values of periodontal parameters of severity in T2D individuals may help clarify some of the controversies regarding the benefit of these medications in this population.